“Determinación de un modelo de cinética de reacción de adsorción de arsénico del suelo de la reserva ecológica los Ilinizas, en la provincia de Cotopaxi durante el periodo 2020- 2021.” - Iles Guamán, Jessica Stefania (2021)
Arsenic has become a global problem and Ecuador is no exception, thus being an environmental challenge when trying to reduce the concentration of this heavy metal in the soil, there is little investigation on removal methods, so it was decided to study the topic. The present research aims to determine a model of arsenic adsorption reaction kinetics from the soil of the Los Ilinizas Ecological Reserve, which is located in the northern part of the reserve in the Cotopaxi province, Ecuador, North coordinates x; 756102 y; 9925455 South x; 756150 and; 9925048 at 4.125 m.s.n.m. In the present study, the field work is carried out as the first part which refers to the sampling in the study place with the random grid method for the 22 points, and then the laboratory work was carried out, which was carried out with the contamination with arsenic trioxide in the laboratory of the Cotopaxi Technical University, for this we worked with a solution of 1 liter and 500 ug/l of initial arsenic, which is within the standard of Remediation Criteria (Maximum Values Permissible) established in ministerial agreement 097A. The reaction equation led to laboratory analysis to obtain the adsorption concentration of As subjected to different stirring times: 0.5, 1, 2, 3, 6, 8, 12, 24 and 48 hours. The colorimetry method was used with the LaMotte Brand arsenic measurement kit. The first order kinetic model was used for the reaction rate. This model showed similar final concentrations, which led to obtaining three models, the most representative being model , corroborated with the coefficient of determination and the margin of error, this three model corresponds to the samples M3-M6-M10-M12-M15 -M17-M20-M22, being giving an adjustable model for concentration in any time interval, it was determined that the soil corresponds to 1% gravel, 63% sand and 32% fine, and Ph 5.56 considering moderately acid, in volatile solids 17.60% of organic matter and for Fe 1450 High, Mn 6.70 medium, Mg 0.90 high, Ca 6, 12 high, Cu 5.90 High and Al concentration at 7.50 which is high, at a height of 4065 m.s.n.m. to 4190 m.s.n.m., giving a 80% of As, adsorption and with such characteristics the reaction rate is 6.18 (ug / Lh).